A Systematic Literature Review: The Influence of Motivation and Work Environment on Employee Performance - Anggraini, Maicha Wulan; Mahgfiroh, Intan Rohmatul; Dagustan, Divara Augis; Putra, Riyan Sisiawan (CV. Proaksara Global Transeduka, 2024)
Employees are the most important asset in a company. Without employees, all of the company's operational activities would cease. Employees need motivation, a supportive work environment, and tasks that allow them to demonstrate their abilities, thereby enabling them to provide their best performance to the company. Employee motivation and performance are two interrelated factors. The more motivation an employee has—whether it is to work, earn money, or support their family—the better their performance at work. This research aims to determine the influence of motivation and the work environment on company employee performance. The method used in this research is a Systematic Literature Review, where motivation and the work environment are the independent variables (x), and performance is the dependent variable (y). All articles referenced in this journal are sourced from Science Direct and Google Scholar, published in the last five years. Based on the results of this research, it can be concluded that there is an influence between motivation and the work environment on employee performance. With motivation, employees will feel more active and enthusiastic, and a positive work environment will further enhance employee performance, ultimately leading to improved company performance.